Navigating the academic landscape: understanding university dynamics, challenges, and strategic responses - Spalanzani, Alain; Zouaghi, Iskander (Journal of Management and Business Education, 2025)
This study investigates the structural and strategic challenges in university governance, focusing on the balance between institutional autonomy and external accountability. Using an inductive, qualitative approach grounded in secondary data analysis and reflective observations from an academic career, the methodology involved thematic coding to identify patterns in university governance, role differentiation, and external influence. Key findings reveal a tension between autonomy and control by government and funding bodies, internal divisions between faculty and administration, and a hierarchical recognition system that prioritizes research roles over teaching-focused ones. These dynamics contribute to internal fragmentation, affecting morale and collaboration. Implications highlight the need for governance models that value diverse contributions, promote cross-functional communication, and enhance adaptability. Limitations include reliance on secondary data and lack of direct interviews, pointing to the need for further research on governance models and faculty engagement. This study provides insights for universities navigating complex educational landscapes while fostering cohesion and strategic adaptability.